PERBEDAAN MODEL BUDIDAYA DENGAN FLUKTUASI KUALITAS AIR UNTUK PERTUMBUHAN UDANG VANAME (LITOPENAEUS VANNAMEI) POLA INTENSIF - Ilham, Mochammad Feryrul; Andayani, Sri; Suprastyani, Heny (JFMR (Journal of Fisheries and Marine Research), 2021)
Water quality can affect the survival and growth of aquatic organisms considering water is a living medium for fish. This study aims to determine how the effect of different models of different ponds on water quality fluctuations for the growth of white shrimp (L. vannamei) intensive pattern. The method used in this study is a comparative descriptive method. The statistical test used is using T test two samples (independent). The main parameters in this study were the results of measuring the growth of white shrimp (L. vannamei) while the supporting parameters in this study were measurements of water quality and total bacteria. The results of this study can be seen that differences in cultivation models have a significant effect on temperature, pH (Power of Hydrogen), DO (Dissolved oxygen), nitrate and have no significant effect on salinity, ammonia and nitrite. The average Specific Growth Rate (SGR) of vaname shrimp in the indoor culture model is 4.5±0.003%/day and the average Growth Rate (GR) is 0.29±0.024 g/day. While the outdoor cultivation model is 3.9±0.003%/day and the average Growth Rate (GR) is 0.26±0.017 g/day.